Ensuring animal welfare in swine breeding - Király, Albert; Wittmann, Mihály (Animal welfare, Ethology and Housing Systems (AWETH), 2005)
With the spreading of intensive pig breeding, pigs got in an artificial milieu, which significantly differed from the natural environment. This effect changed their behaviour. Through this change, profitability and safety of pork production decreased. Methods developed by the ethologists lead us how to repair the faults and deficiencies and improve the welfare of animals and consequently how to increase the performance. It is an important aspect to guarantee freedom for the animals in lying, in bed choosing, in standing, in motion, in stretching, in turning over and in washing themselves.